Critical review of multidisciplinary non-surgical local interventional ablation techniques in primary or secondary liver malignancies - Kovács, Attila; Iezzi, Roberto; Cellini, Francesco; Lancellotta, Valentina; Bischoff, Peter; Carchesio, Francesca; Tagliaferri, Luca; Kovács, György; Gambacorta, Maria (Journal of Contemporary Brachytherapy, 2019)
Local non-surgical interventional percutaneous ablation represents nowadays an important part of the potential treatment strategies. Although surgical ablation represents the gold standard, in the past decade there was an expansion in the use of non-surgical ablative techniques: radiofrequency, microwave, laser, cryoablation, irreversible electroporation, and interventional radiotherapy (brachytherapy) in primary as well as secondary liver cancers. With the growing experience in the field, there was implemented a new pillar for cancer treatment, together with surgery, chemotherapy as well as radiotherapy, so-called interventional oncology (IO). To date, there are no published papers regarding a comparative interdisciplinary evaluation of all these non-surgical interventional local ablation therapies. Our paper offers a critical interdisciplinary overview of the treatments in both primary and secondary liver tumors, including from a cost-effective point of view. Furthermore, the present status of education in IO and a comparison of actual economic aspects of the treatments are also provided.